A New Sensitive Method for the Detection of Mycoplasmas Using Fluorescence Microscopy - Ligasova, Anna; Vydržalová, Markéta; Burianova, Renata; Brůčková, Lenka; Vecerova, Renata; Janostakova, Anna; Koberna, Karel (MDPI, 2019)
Contamination of cell cultures by mycoplasmas is a very common phenomenon. As they can substantially alter cell metabolism and potentially spread to all cell cultures in laboratory, their early detection is necessary. One of the fastest and cheapest methods of mycoplasma detection relies on the direct staining of mycoplasmas’ DNA by DAPI or Hoechst dyes. Although this method is easy and fast to perform, it suffers from the low signal provided by these dyes compared to the nuclear DNA. Therefore, the reporter cell lines are used for cultivation of mycoplasmas before DAPI or the Hoechst staining step. In the study presented, we have developed and tested a new immunofluorescence assay for the detection of mycoplasmas. The method is based on the enzymatic labeling using DNA polymerase I and modified nucleotides utilizing nicks in the mycoplasmas’ DNA. Modified nucleotides are incorporated into mycoplasmas’ DNA and subsequently visualized by immunofluorescence microscopy. The developed approach is independent of the mycoplasma strain, does not intensely stain nuclear DNA, does not stain other bacteria, and provides higher sensitivity than the approach based on the direct labeling using DAPI or Hoechst dyes.
Nová citlivá metoda k detekci mykoplazmat využívající fluorescenční mikroskopii
Keywords: cell cultures; mycoplasma infection; immunofluorescence detection; buněčné kultury; mykoplazmové infekce; imunofluorescenční detekce